Abdominal wound length influences the postoperative serum level of interleukin-6 and recovery of flatus passage among patients with colorectal cancer - Tsai, Po-Li; Chen, Jian-Syun; Lin, Chi-Hsin; Hsu, Tzu-Chi; Lin, Yu-Wen; Chen, Ming-Jen (Frontiers in Surgery, 2024)
Introduction: A mini-laparotomy for colorectal cancer (CRC) has been reported to shorten postoperative ileus (POI) and hospital stay. Interleukin-6 (IL-6) plays a role in intestinal tissue inflammation, leading to POI. This study investigated the effects of abdominal wounds and IL-6 levels on POI in patients having CRC surgery.Materials and methods: Forty-three patients with CRC underwent bowel resection.Serum samples were collected preoperatively and at 2, 24, and 48 h after surgery for cytokine quantification by ELISA. Clinical data, including time from surgery to first passage of flatus and postoperative hospital stay, demographic and pathological data, and routine blood tests, were compared statistically with abdominal wound length and the postoperative increments of cytokines (designated as △). Results:The length of the abdominal wound showed a significant correlation with clinical variables (length of operation time, time of first flatus passage, and length of postoperative hospital stay) and cytokine variables (IL-6(△2h), IL-8(△2h) and IL-10(△2h). Linear regression analysis showed that the abdominal wound length significantly influenced the operation time, time of first flatus passage, and length of postoperative hospital stay (p < 0.001). The length of the abdominal wound showed a significant influence on the IL-6(△2h) and IL-8(△2h) (p < 0.001, respectively) but no influence on IL-10(△2h). IL-6(△2h), but not IL-8(△2h), significantly influenced the time to first flatus passage and length of hospital stay (p = 0.007, p= 0.006, respectively). The mini-laparotomy approach (wound length < 7 cm) led to significantly shortened operation time, time of first flatus passage, length of postoperative stay (p = 0.004, p = 0.003, p = 0.006, respectively) as well as reduced postoperative increment of IL-6(△2h) (p = 0.015). The mini-laparotomy for anterior resection surgery significantly influenced operation time, time of first passage of flatus, length of postoperative stay, and IL-6(△2h). Conclusion: Our study is the first to report the complex interaction among the length of the abdominal wound, IL-6 serum level, recovery of the first passage of flatus, and postoperative hospital stay. These results suggest that smaller abdominal wounds and smaller postoperative IL-6 increments were associated with faster recovery of flatus passage and shorter hospital stays.